PENGARUH WHISTLEBLOWING, BUDAYA, DAN RELIGIUSITAS TERHADAP PENCEGAHAN FRAUD ORGANISASI MAHASISWA: MORAL SEBAGAI MODERATOR - Khaira, Nurul; Aditiani, Clarisa May; Afifah, Annisa Nur (Jurnal Riset Akuntansi, 2025)
Fraud  in  financial  reporting  in  organisations  often  occurs.  Fraudulent  behaviour  can  harm  the  credibility  and  sustainability  of  an  organisation.  This  study  aims  to  determine  the  effect  of  whistleblowing  system,  organisational  culture,  and  religiosity  on  fraud  prevention  in  financial  reporting  of  student  organisations  at  Ahmad  Dahlan  University,  individual  morality  as  a  moderating  variable.  The  method  of  analysis  used  in  this  study  is  through  analytical  tests  in  the  form  of  outer  model  and  inner  model  and  moderated  regression  analysis  (MRA)  by  utilising  SmartPLS  3.0  software.  The  results  of  this  study  indicate  that  first,  the  whistleblowing  system  has  a  positive  effect  on  fraud  prevention.  Second,  organisational  culture  has  a  positive  effect  on  fraud  prevention.  Third,  religiosity  has  no  effect  on  fraud  prevention.  Fourth,  individual  morals  are  unable  to  moderate  the  relationship  between  the  whistleblowing  system,  organisational  culture  and  religiosity  on  fraud  prevention.  This  research  is  expected  to  provide  an  overview  of  the  influence  of  fraud  behaviour  in  the  financial  reporting  of  student  organisations.  Keywords:  whistleblowing,  organisational  culture,  religiosity,  fraud  prevention